Cellular and molecular mechanisms of tooth root development - Li, Jingyuan (Development, 2017)
The tooth root is an integral, functionally important part of our dentition. The formation of a functional root depends on epithelial-mesenchymal interactions and integration of the root with the jaw bone, blood supply and nerve innervations. The root development process therefore offers an attractive model for investigating organogenesis. Understanding how roots develop and how they can be bioengineered is also of great interest in the field of regenerative medicine. Here, we discuss recent advances in understanding the cellular and molecular mechanisms underlying tooth root formation. We review the function of cellular structure and components such as Hertwig's epithelial root sheath, cranial neural crest cells and stem cells residing in developing and adult teeth. We also highlight how complex signaling networks together with multiple transcription factors mediate tissue-tissue interactions that guide root development. Finally, we discuss the possible role of stem cells in establishing the crown-to-root transition, and provide an overview of root malformations and diseases in humans.